Hill-Type Formula and Krein-Type Trace Formula for Hamiltonian Systems (Analysis in Theory and Applications, 2022)
In this paper, we give a survey on the Hill-type formula and its applications.  Moreover, we generalize the Hill-type formula for linear Hamiltonian systems and Sturm-Liouville systems with any self-adjoint boundary conditions, which include the standard Neumann, Dirichlet and periodic boundary conditions. The Hill-type formula connects the infinite determinant of the Hessian of the action functional with the determinant of matrices which depend on the monodromy matrix and boundary conditions. Further, based on the Hill-type formula, we derive the Krein-type trace formula. As applications, we give nontrivial estimations for the eigenvalue problem and  the relative Morse index.
Keywords: Hill-type formula; trace formula; conditional Fredholm determinant; relative Morse index.